Revitalizing Ethiopia and Russia’s Bilateral Relations - NARDOS HAWAZ YEHEYS (Ученые записки Института Африки Российской академии наук)
Since its successful establishment in 1898, the diplomatic relations between Ethiopia and Russia were interrupted gently, but instantly revived in 1943. The two countries have traditionally enjoyed fruitful political, social, and economic ties over the past 100 memorable years. Russia has undoubtedly made significant strides in public relations, education and medicine since the modernization of agriculture in the economic sector, it has generously helped Ethiopia by progressively expanding the guiding principle of a mixed economy. In the modern political arena, the former Soviet administration had typically offered its necessary support for Ethiopia through ideological and military expansion. And even so, Russia has repeatedly demonstrated its historic commitment in various international forums. This relationship is growing more causal. They have presently developed into scientific cooperation and reached an agreement to establish a nuclear power plant in Ethiopia. What constitutes the official status of diplomatic relations between the two countries? In what areas is the cooperation more effective? And what represent the determination of the governments? The study examines the historical relationship between the two countries, studies cooperation agreements, and checks actual records to explain these fundamental questions. The analysis is typed in the qualitative method and uses secondary data as a reference.